Analisis Komparasi Kinerja Keuangan PT Bank BTPN. Tbk Sebelum dan Sesudah Merger - Nike Anabella; vera Intanie dewi (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2023)
The purpose of this study is to conduct a comparative test of Bank BTPN Tbk.,financial performance before and after the merger using the Risk-Based Bank Rating approach. The method used is verificative study, carried out by conducting a paired t-test of two samples. This study found that Bank BTPN Tbk. financial performancedeclined after the merger. This is indicated by the increasing LDR, indicating that the bank's liquidity risk becomes greater after the merger. The NIM and ROA ratios were smaller and the BOPO ratio increased after the merger, indicating that Bank BTPN Tbk. ability to generate profits has decreased. The level of bank capital with the CAR indicator also decreased. Based on the results of comparative analysis, it can be proven that there are differences in the financial performance of Bank BTPN between before and after the merger